Menggali Akar Permasalahan: Konflik Antara Tukang Ojek Konvensional Dan Tukang Ojek Online Di Stasiun Jember - Alvina Setiyawati; Ani Linta Sari; Ardhia Pramesty Regita Cahyani (Badan Penerbit STIEPARI Press, 2023)
Ojek is a transportation service that has long been the choice of people to travel. Along with the development of technology, currently ojek develops into two types, namely conventional motorcycle taxis and online motorcycle taxis.However, in recent times conventional motorcycle taxis have begun to face a decline in popularity along with the emergence of online motorcycle taxis. One of them is a conventional motorcycle taxi in front of Jember station. So this causes conflicts due to passengers preferring to use online motorcycle taxis compared to conventional motorcycle taxis. The reason they choose online motorcycle taxis is because what is offered is considered more economical and sometimes offers promos that make online motorcycle taxi fares cheaper than conventional motorcycle taxis. This certainly makes conventional motorcycle taxis experience a decrease in income. This study used qualitative research methods, where data were collected through field observations, interviews, and voice recordings, and refer to previous studies. This study uses Dahrendorf conflict theory to analyze conflicts that arise between conventional motorcycle taxis and online motorcycle taxis in the Jember station area, where differences in status and access rights set by local authorities are the main focus in this study.